Anions of xenon clusters bound by long-range electron correlations - Bezchastnov, Victor G.; Vysotskiy, Victor P.; Cederbaum, Lorenz S. (Physical review letters, 2011)
In contrast with the single atom, atomic van der Waals clusters can form stable anions where the excess electron is bound due to long-range correlations with the electrons of the cluster. We report on extensive all-electron many-body ab initio studies on Xe clusters. Three-dimensional, planar, and linear structures of the clusters are investigated and compared. In particular, we find that the minimal number of Xe atoms in the cluster required to form a stable anion is 5 independently of the dimensionality of the cluster. We provide electron affinities for clusters made of 5, 6, and 7 atoms in all dimensions and find that the planar clusters form the most stable anions. The Dyson orbitals of the excess electrons are computed and analyzed.
Gesehen am 23.03.2022